ANALISIS PENDAYAGUNAAN ZAKAT DALAM PENGENDALIAN PANDEMI COVID-19 PERSPEKTIF MAQASHID SYARIAH - Taufiqur Rahman; Alan Su'ud Ma'adi (istinbath, 2023)
The focus of this research is to examine the utilization of zakat in controlling the covid-19 pandemic which is analyzed through the maqashid sharia approach in BAZNAS and LAZISMU Pamekasan Regency.This research includes field research that uses qualitative methods with qualitative descriptive research properties. The method of data collection using interviews, observation and documentation. Then the primary and secondary data obtained were analyzed using qualitative data analysis with three processes, namely data reduction, data presentation and conclusion drawing.The results of this study that the utilization of zakat in the Amil Zakat Agency (Baznas) and Lazismu Kab. Pamekasan plays a role in controlling the Covid-19 pandemic in Pamekasan Regency by distributing it to three sectors: First, Health, Second, Economy, Third, Education in the form of consumptive and productive. Then the role of its utilization has been in accordance with the objectives of the stipulation of zakat in the aspects of worship and the economy that reaches maqashid sharia.